Early foreign language education – the sooner the better? - Sopata, Aldona (Glottodidactica, 2010)
The article aims to summarize investigations which shed some light on the mechanisms of early second language acquisition and to draw from them pedagogical implications. Developing an optimal outline for foreign language teaching in early childhood should involve factors which make possible the use of inductive mechanisms of language acquisition by children.